2009
DOI: 10.1158/1078-0432.ccr-08-2317
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on Light Dosimetry Variables for Photodynamic Therapy of Barrett's Esophagus with High-Grade Dysplasia

Abstract: Purpose: Photodynamic therapy (PDT) is used to treat Barrett's esophagus with high-grade dysplasia and mucosal carcinoma. Outcomes are variable with some patients having persistent disease, whereas others develop strictures. The aims of this study were (a) to compare porfimer sodium tissue uptake, light dose, and esophageal thickness with clinical outcomes and (b) to determine the selectivity of porfimer sodium uptake in diseased and normal epithelium. Experimental Design: Forty-eight hours after porfimer sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A similar study supports this data by stating PDT proved effective in treating smaller BE or ADC lesions but complete ablation was less likely with lesions over 3 cm in length [ 153 ]. Maybe even more important than BE length is esophageal wall thickness, as thicker walls have a lower chance of achieving successful results with Photofrin ® -PDT [ 154 ].…”
Section: Pdt In Clinical Trialsmentioning
confidence: 99%
“…A similar study supports this data by stating PDT proved effective in treating smaller BE or ADC lesions but complete ablation was less likely with lesions over 3 cm in length [ 153 ]. Maybe even more important than BE length is esophageal wall thickness, as thicker walls have a lower chance of achieving successful results with Photofrin ® -PDT [ 154 ].…”
Section: Pdt In Clinical Trialsmentioning
confidence: 99%
“…In preliminary experiments, mice were treated under some of the strongest (i.e., with respect to the product of PS dose and light fluence, from the simplified formula of photodynamic dose [22]) conditions of the matrix (i.e., no. 6, 7, and 11).…”
Section: Validation Of the Experimental Matrixmentioning
confidence: 99%
“…Further, VLE provides high-resolution, 2-dimensional imaging information, which may be useful to characterize the thickness of BE mucosa to determine an optimal endoscopic treatment modality, such as the thinlayer radiofrequency ablation or deeper ablation with cryotherapy or photodynamic therapy. [35][36][37] The current multicenter, prospective study, performed in patients with known or suspected BE, has demonstrated that the Nvision VLE Imaging System effectively achieved completed scans (full 6-cm pullback that typically included the proximal stomach, gastroesophageal junction, and distal esophagus) in most cases (87%). These scans were performed during screening or surveillance upper endoscopy procedures and provided the physician with contemporaneous images of the distal esophageal mucosa and submucosa.…”
Section: Discussionmentioning
confidence: 94%